Belzec, Sobibor, Treblinka : The Operation Reinhard Death Camps - Arad, Yitzhak, 1926-2021 (Book collections on Project MUSE., 1999)
""... Mr. Arad reports as a controlled and effective witness for the prosecution.... Mr. Arad's book, with its abundance of horrifying detail, reminds us of how far we have to go.""-New York Times Book Review""... some of the most gripping chapters I have ever read.... the authentic, exhaustive, definitive account of the least known death camps of the Nazi era."" -Raul HilbergArad, historian and principal prosecution witness at the Israeli trial of John Demjanjuk (accused of being Treblinka's infamous ""Ivan the Terrible""), uses primary materials to reveal the complete story.